Malignant infantile osteopetrosis: A rare cause of refractory hypocalcemia - Niraj Kumar Dipak; Nadia Shagufta (Wolters Kluwer Medknow Publications, 2023)
Background: Infantile malignant osteopetrosis (IMO) is a rare autosomal recessive disease characterized by a higher bone density in bone marrow caused by the dysfunction of bone resorption. Clinical Description: A 2-month-old baby boy presented with features of lower respiratory tract infection, along with a swollen right upper arm due to fracture of humerus, along with signs of bicytopenia and hepatosplenomegaly. He had a history of hypocalcemic seizures at 8th day of life. Management and Outcome: Current hospitalization revealed refractory hypocalcemia and hypophosphatemia with normal to increased Vitamin D and parathormone levels and increased density of bone. Hypocalcemia was particularly refractory in nature needing multiple intravenous calcium corrections. Whole exome sequencing detected compound heterozygous variants in the T-cell immune regulator 1 pathogenic gene of IMO. Simultaneously, a heterozygous nonsense variation in exon 4 of the CHRNA4 gene was detected causing nocturnal frontal lobe epilepsy. As the infant had evidence of bone marrow failure, he was considered and referred for hematopoietic stem cell transplantation. Conclusion: Neonatal and early infantile hypocalcemia are commonly seen by pediatricians, but an etiology of IMO is rarely considered. The presence of fracture of long bones with cytopenias and hepatosplenomegaly in a young infant with recurrent hypocalcemia, without Vitamin D deficiency, should raise suspicion of this disorder and genetic analysis should be carried out for the same.